Artful and Contorted Coordinating: The Ramifications of Imposing Formal Logics of Task Jurisdiction on Situated Practice - Pine, Kathleen H.; Mazmanian, Melissa (Academy of Management Journal, 2017)
Ongoing coordination is the backbone of work process and organizational effectiveness. Coordinating requires that interdependent specialists achieve integrating conditions for coordination—including understanding who is accountable for carrying out a given task, how a sequence of actions should proceed, and how one’s work fits into the whole on an ongoing basis. Navigating the inevitable disconnect between formal logics of action and the specifics of the local context and situation at hand is a hallmark of effective coordinating. Nevertheless, as work systems designed to direct action with a heavy hand are increasingly implemented in organizations, the disconnect between formal delineations and situated practice is transformed with large negative consequences for organizations. Through 16 months of empirical research using ethnographic methods surrounding implementation of an electronic health records (EHR) system in a hospital obstetric unit, we find that the EHR rendered what was once a productive disconnect between formal logics and situated practice into an unproductive disconnect. Further, this shift engendered a new form of ongoing coordinating. What was once “artful coordinating”—in which clinicians across occupations drew upon formal logics, local context, and situated contingencies as resources to action and, in so doing, created conditions of predictability and informal accountability—became “contorted coordinating,” characterized by working around formal logics of the EHR while struggling to meet the demands of local context and situated contingencies, thus undermining predictability.